Femoral derotation osteotomy—Does intraoperative electromagnetic tracking reflect the dynamic outcome?. Issue 6 (3rd September 2021) - Geisbüsch, Andreas; Götze, Marco; Putz, Cornelia; Dickhaus, Hartmut; Dreher, Thomas
Abstract: Femoral derotation osteotomy (FDO) is a well‐established procedure for the correction of internal rotation gait in children with cerebral palsy. Various studies have demonstrated good results for FDO both in short‐term and long‐term evaluation with some describing recurrence and over‐ or under‐corrections. The present study evaluates the use of an objective intraoperative derotation measurement through electromagnetic tracking. We report the static and dynamic results of 11 cases with internal rotation gait (8 male, 3 female, mean age 22.2 years), that underwent FDO with intraoperative electromagnetic tracking and conventional goniometric measurement of the correction. The dynamic and static changes were assessed through three‐dimensional gait analysis after a mean of 12 months after surgery and rotational imaging preoperative and after a mean of eleven days postoperatively. Mean hip rotation in stance significantly decreased from 20.9° ( SD 5.9) to 5.8° ( SD 4.7°) after FDO. The mean amount of derotation quantified by electromagnetic tracking was 23.2° (16.5°–28.8°) and 25.1° (20.0°–33.0°) for goniometric measurement. Both measurement modalities showed small differences to rotational imaging (electromagnetic bone tracking [EMT]: 0.72°; goniometer: 1.19°) but a large deviation when compared to three‐dimensional gait analysis (EMT: 8.5°, goniometer: 9.1°). In comparison to the static changes and EMT measurement, the dynamic changes measured during 3‐D‐gait analysis reflected only 66% of the actual derotation performed during surgery. Although electromagnetic tracking allows a precise intraoperative assessment of the derotation during FDO, the amount of intraoperative correction is not reflected in the improvements in three‐dimensional gait analysis.